Strategi Komunikasi Pemasaran Golf Course Teringbay Nongsa dalam peningkatan Kunjungan Pasca Covid 19 - -, Ranisha Dwinata; Abidin, Sholihul (SCIENTIA JOURNAL, 2023)
Tourism is undeniably one of the major contributors to a country's economy, making its development crucial.Among the tourism sectors that significantly contribute to national revenue is the sport of golf. Therefore, thisresearch aims to investigate the marketing communication strategies of Golf Course Teringbay Nongsa inenhancing post-COVID19 visits and aiding the national economy. The study utilizes informant interviews toexamine the various forms of implementing marketing communication strategies at Golf Course TeringbayNongsa, employing the Integrated Marketing Communication theory as the conceptual framework. Thefindings provide valuable insights into the effectiveness of the applied strategies in attracting visitors amidstthe challenges posed by the pandemic and their potential impact on the economic growth of the nation